The Disability Rights Movement in Germany: History, development, present state - K, Swantje (Disability Studies Quarterly, 2006)
Having gradually emerged during the late 1970s the (West) German Disability Rights Movement was "born" with a big bang in 1981, the UN Year of the Disabled. This paper explores the background from which the movement emerged and describes its subsequent development. From the very beginning, the goals of the movement were the de-medicalization of disability, self-determination, anti-discrimination and equalization, securing disabled people's right to life, integration into the community, and as much control as possible over services for disabled people. After the action-packed year of 1981, the movement settled down to everyday business: A lot of groups started to organize practical help like counseling and assistance services, some individuals decided to get involved in politics, and even others did research on eugenics and bioethics. Quite early in the movement's history disabled women began to form their own "sub-movement," which was quite successful. Recently, Disability Studies and their implementation in the German academic field have become an issue. These "branches" of the movement have sometimes crossed and intertwined, thus forming a strong national Disability Rights Movement. After the reunification of East and West Germany in 1990, disabled people from the former German Democratic Republic (GDR) joined the already existing movement.